Dynamics of two microscale DPF devices. (15th December 2015) - Pollard, William; Duggleby, Andrew; Staack, David
Abstract: Dense plasma focus (DPF) devices are coaxial transient discharge devices capable of generating plasma densities greater than 10 16 cm −3 with ion temperatures in excess of 1 keV by compression resulting from strong magnetic fields created by high pulsed current. They are predominately used for high energy particle generation, but they are also convenient for investigating pinch dynamics due to their relatively fast repetition rates. These devices have been extensively studied at length scales on the order of cm, and this work helps to bridge understanding of larger low pressure pinches and more recent moderate energy density sources with novel applications like portable sources for high energy particles. In this research, the dynamics of two significantly smaller DPF devices operating in 50–190 torr He at  <5 J/pulse with anode radii of 550 μ m and 100 μ m have been investigated using a 50 ns gated ICCD to image discharges throughout their lifetimes. Typical discharge stages of breakdown, rundown, pinch and expansion are observed for the microscale DPF. Images during the breakdown process are compared with respect to their symmetry, the velocity of their features, and their relative pinch intensities. Applicable scaling parameters are also compared to those of other DPF devices. In addition, the applicability of Knudsen scaling to DPF operation is introduced. The images show that as the anode radius decreases, breakdown and rundown features tend towards symmetry at higher pressure and near the Paschen minimum.